Analisis Pengaruh Tingkat Pertumbuhan Asset, Profitabilitas, dan Ukuran Perusahaan terhadap Struktur Modal (Studi Empiris Perusahaan Sektor Pertambangan di Bursa Efek Indonesia) - Rahmiati, Rahmiati; Yumna, Aimatul; Gusti, Mia Ayu (Jurnal Kajian Manajemen Bisnis, 2016)
The purpose of this research is to determine 1) the effect of asset growth rate to capital structure of mining companies listed in Indonesia Stock Exchange 2) the effect of profitability to capital structure of mining companies listed in Indonesia Stock Exchange 3) the effect of firm size to capital sructure of mining companies listed in Indonesia Stock Exchange. The research sampel are 76 mining companies listed in Indonesia Stock Exchange around 2011-2014. This research used purposive sampling method. The statistical methods used in this research are multiple regressions. The results of this reseach indicate that: (1)Â  asset growth rate have negative and no significant effect to capital structure of mining companies listed in Indonesia Stock Exchange (2) profitability have negative and significant effect to capital structure of mining companies listed in Indonesia Stock Exchange and (3) firm size have positive and significant effect to capital structure of mining companies listed in Indonesia Stock Exchange.Â